Leadership Contribution to Organizations During Pandemic Disruption : a case Study of Private Swedish Organizations - Fakhro, Ismail (SLU/Dept. of Forest Economics, 2021)
Organizations globally faced a disruption throughout the pandemic outbreak from December 2020 onwards. Following the outbreak, regulations and measurements to stop the Covid-19 have been imposed on some sectors, while they remained as recommendations in others. The Swedish private sector faced a unique situation due to the contrasting decisions to keep the country without a lockdown took by the Swedish government. As a result, organizations faced both challenges and opportunities trying to deal with this disruption. The study focuses on the importance and guidance of various leadership styles throughout this process, and what type of challenges and opportunities did they face, to bring a foundation that can be used locally or globally in assisting leaders to drive through the pandemic outbreak. This foundation consists of identifying both transactional and transformational leadership with their traits, and how did each leader from both sides, the transactional and transformational leadership, react to the challenges. The study found that transformational leadership was more effective in the studied case to target team motivation and inspiration within good resources, while transactional leadership was more effective in organizational survival in the case of limited resources. In conclusion, there is no one-fits-all style, and leaders must mix both styles depending on the case of each time and disruption, to ensure proper leadership and achieve higher team engagement and performance.